Journey to Gonzales - Cuate, Melodie A. (Book collections on Project MUSE., 2008)
When Mr. Barrington's trunk transports Nick, Hannah, and Jackie to Gonzales, Texas, in 1835, the girls end up in a military camp and learn about life in the Mexican army, while Nick participates in events leading up to the Battle of Gonzales.